Răspuns :
a) 2x+2-5=x-3 echivalent cu 2x-3=x-3 echivalent cu 2x-x=3-3 echivalent cu x=0
b)3+5x-10=3x-7 echivalent cu 5x-7=3x-7 echivalent cu 5x-3x=7-7 echivalenrt cu 2x=0 x=0
c)4x+12-7=3x-7 echivalent cu 4x+12-7+7=3x echivalent 4x+12=3x rezulta x=12
b)3+5x-10=3x-7 echivalent cu 5x-7=3x-7 echivalent cu 5x-3x=7-7 echivalenrt cu 2x=0 x=0
c)4x+12-7=3x-7 echivalent cu 4x+12-7+7=3x echivalent 4x+12=3x rezulta x=12
a)
2(x+1)-5=x-3
2x+2-5=x-3
2x-x= 5-2-3
x=0
b) 3+5(x-2)=3x-7
3+ 5x-10=3x-7
5x-3x= 10-7-3
2x=0
x=0
c) 4(x+3)-7=5x-1
4x+12-7=5x-1
12-7+1=-5x-4x
6=x